Regression analysis of transportation infrastructure development using Transit Oriented Development concept - Sirojuzilam, Noer Fadhly, Rahim Matondang,; Saleh, Sofyan M. (Opción, 2019)
The aim of the study is to analyzetransportation infrastructure development in Banda Aceh city of Indonesia using Transit Oriented Development (TOD) concept. The type of research applied is quantitative by using path analysis. The data used to model the development of transportation infrastructure and the spatial structure with the concept of TOD. From the model obtained by Banda Aceh city which is a region of homogeneous region type is characterized by the existence of the relative similarity in the region and has not yet characterized the layout with the transit oriented development (TOD) concept.